Key concepts in classical social theory - Law, Alex (SAGE Key Concepts, 2012)
"In Key Concepts in Classical Social Theory, individual entries introduce, explain and contextualize the key topics within classical social theory. Definitions, summaries and key words are developed throughout with careful cross-referencing, allowing students to move effortlessly between core ideas and themes. Each entry provides: clear definitions, lucid accounts of key issues, up-to-date suggestions for further reading, and informative cross-referencing."-Provided by publisher.